Meneropong Indonesia: Sebuah Analisis Sosiologis dan Psikologis Atas Konflik Benuansa Keagamaan Di Indonesia - Triana Rosalina Noor (Universitas Islam Tribakti Lirboyo Kediri, 2018)
Indonesian is a pluralistic nation, such as religion. The essence of religion is teaching followers for helping each other to keeping the unity of Indonesia. Religion will encourage its people for kindness to humanity eventough on the same religion or different religions. In fact nowdays, religious conflict is inevitable to happen in Indonesia. A religious conflict or even a conflict that is made as can be as threath to disintegrity of Indonesia.Facing religious conflict in Indonesia is required analysis from various angles such as sociology and psychology aspects of the religious conflict. The study concluded that the causes of religious conflict are caused by economic factors, social prejudices, conflicy of interests and others. This sociological and psychological analysis can be used as an illustration of the actions that can be done for resolving religious conflict as well as the effort to re-engage the unity to prevent the disintegration of Indonesia.